1998
DOI: 10.1023/a:1006566810636
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Our previous kinetic and thermodynamic studies upon the reactional system HCHO/HCN/NH3 in aqueous solutions are completed. In the assumed prebiotic conditions of the primitive earth ([HCHO] and [HCN] near 1 g L-1, T = 25 degrees C, pH = 8, [NH3] very low), this system leads to 99.9% of alpha-hydroxyacetonitrile and 0.1% of alpha-aminoacetonitrile (precursor of the alpha-amino acid). The classical base-catalyzed hydration of nitriles, slow and not selective, can not modify significantly this proportion. On the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 81 publications
(50 citation statements)
references
References 20 publications
0
46
0
1
Order By: Relevance
“…The preceding model is theoretical, but can be applied to concrete chemical systems of amino acid derivatives. In a prebiotic point of view, amino acids are known to be synthesized abiotically in many ways (27)(28)(29)(30). However, the formation of the first prebiotic peptides is not a trivial problem, as free amino acids are poorly reactive.…”
Section: Resultsmentioning
confidence: 99%
“…The preceding model is theoretical, but can be applied to concrete chemical systems of amino acid derivatives. In a prebiotic point of view, amino acids are known to be synthesized abiotically in many ways (27)(28)(29)(30). However, the formation of the first prebiotic peptides is not a trivial problem, as free amino acids are poorly reactive.…”
Section: Resultsmentioning
confidence: 99%
“…[323][324][325][326][327][328][329][330] These authors found that carbamoyl amino acids easily react with NO/O 2 gas mixtures to form NCAs in almost quantitative yields (Scheme 38). The carbamoyl amino acids (CAAs) result from the reaction of amino acids with cyanate ions, a prebiotic scenario that has been discussed in detail.…”
Section: Ncas and The Hypothesis Of Molecular Evolutionmentioning
confidence: 99%
“…The examples mentioned here demonstrate their ability to catalyze some reactions of bifunctional substrates very efficiently (a characteristic of most biochemical compounds), α-amino acid derivatives in particular. A striking indication of the involvement of these molecules in the processes from which life arose is the fact that aldehyde catalysis was demonstrated as the predominant pathway [20,96] for the hydration of α-amino nitriles in Miller's experiment showing the formation of amino acids under prebiotic conditions. [97] The hypothesis that catalysis through induced intramolecularity has played an important role in the processes resulting in the emergence of life therefore seems quite reasonable.…”
Section: The Emergence and Evolution Of Enzymesmentioning
confidence: 99%